Perceptions and Barriers to Contraceptive Use among Adolescents: A Case Study from Nairobi, Kenya - Kinaro, Joyce; Kimani, Murungaru; Ikamari , Lawrence; Ayiemba, Elias H. O. (Current Overview on Disease and Health Research Vol. 6, 2022)
The present study aimed to identify the barriers affecting the use of contraception among adolescents in school and out of school, married and unmarried adolescents. Adolescence is a unique period of transition between childhood and adulthood, an important time to shape behavior and norms, including the development of positive practices for future good health and well-being To understand the roles of perceptions and barriers on contracep- tive use, a mixed method study design was applied to a conceptual framework that operationa- lized these concepts using data from different sources of social interactions in Nairobi, Kenya. Quantitative data were collected from 1119 adolescents aged 15 - 19 years. Qualitative data were collected from adolescents, adolescents’ parents and their school teachers. The latter were analyzed and interpreted together with the results from cross-tabulations and logistic regression in order to understand the roles of perceptions and barriers. Contraceptive use was found to be 8.6 percent among the adolescents. Overall, poor contraceptive use appeared to be influenced by unfavorable opinions held by parents, teachers, and teenagers. In contrast to hurdles like communication between sexual partners, attitudes toward adolescents using contraceptives, and the capacity to access contraceptives, negative impressions played a larger role. Qualitative results demonstrate that teachers and parents lack the knowledge and expertise necessary to tackle sexuality-related topics. Linking data among adolescents, parents and teachers help to understand the roles of perceptions and barriers to contraceptive use in Kenya. The findings suggest capacity building of teachers and parents on accurate sexuality information for adolescents while services should be youth-friendly.